Food standards in trade agreements: Differing regulatory traditions in the EU and the US and tips for the TTIP - Bettina Rudloff (Stiftung Wissenschaft und Politik (SWP), 2014)
The European Union is both the largest exporter and importer of agricultural products in the world. Its major trading partners are the United States, Argentina, Brazil, Russia, and China. This trade in agricultural products is influenced by a number of political measures. In addition to tariffs, trade in foodstuffs is increasingly influenced by so-called nontariff measures (NTMs), among which are threshold values for pesticide residues, production standards, and packing- and labeling standards. In fact, such measures can impact the costs of trade much more than tariffs. Reducing these NTMs within the Transatlantic Trade and Investment Partnership (TTIP) offers enormous prospects for economic growth. (SWP Comments)
Keywords: 320